ENDOVASCULAR MANAGEMENT OF LIFE-THREATENING CAROTID BLOWOUT SYNDROME AFTER OSTEORADIONECROSIS OF THE MANDIBULA — A CASE REPORT AND LITERATURE REVIEW - Coelho, Andreia (2018)
Aim: Carotid blowout syndrome is a rare but devastating complication of head and neck malignancy, and is associated with a reported mortality and neurologic morbidity of 40% and 60% respectively. The aim of this case report is to present our experience with a single case of massive haemorrhage from the internal carotid artery (ICA) in a previously irradiated neck treated with a stentgraft, hence maintaining carotid artery patency. Methods: Relevant medical data were collected and literature review was performed. Results: The patient is a 61-year-old male with a previous history of head and neck cancer submitted to radical surgery and chemo and radiotherapy. Seven years later, the patient was diagnosed with osteoradionecrosis of the mandibula and submitted to surgery. Hospital stay was prolonged due to local infection and suture dehiscence with carotid artery exposure. No previous episodes of sentinel bleeding were registered. Life-threatening haemorrhage from the surgical wound started acutely. Under manual compression, the patient was rushed to the angiography suite and the diagnostic angiography ascertained active bleeding from the ICA. A stentgraft Atrium Advanta V12 (Maquet Getinge group, Hudson, NH, USA) was deployed maintaining ICA patency. The patient was subsequently submitted to surgical reconstruction and had an uneventful recovery. Discussion: Management of acute carotid blow syndrome is critical, often requiring a multidisciplinary approach. Stentgraft placement is a highly feasible and effective approach with lower morbimortality rates when compared to surgical repair/ ligation or endovascular embolization. However long term results with patency rates are currently lacking.